METHODS OF PRESETING BOUNDARY CONDITIONS AND GEOMETRY OF THE SCREW-PROPELLER IN THE FLOW VISION - Kornelyuk, O. N. (Science and Transport Progress, 2018)
Purpose. The article is aimed to: generate 3D models of the screw-propellers under study, as well as the calculation box; carry out a series of numerical experiments to verify the obtained results with the corresponding results of the model experiments; study possible ways of setting a project to simulate the screw-propeller operation in free water; to evaluate the efficiency of the ways of project setting. Methodology. The analysis of possibilities and features of CFD-modeling using the example of studying the screw-propeller operation in free water is carried out. As a result, the ways of defining the boundary conditions and the geometry of the screw-propeller in the calculating project are revealed and analyzed for the reliability of the obtained calculation results. Recommendations on the use of the methods for setting the project for simulation of the screw-propeller operation in free water are formulated. Findings. Using the example of solving a practical problem on studying the influence of the screw-propeller geometry on its hydrodynamic efficiency, the expediency of CFD-technologies introduction into the design of screw-propellers is substantiated. This is evidenced both by numerical results and by visualization of the velocity and pressure distributions during the water stream flow around the screw-propeller. For the research, the screw-propellers with different profiling were used. The method using the sector model of the screw-propeller is the most inefficient way of setting the project for simulation of the screw-propeller operation. Originality. The results of the work are the part of the methodology for setting the project in the Flow Vision environment for conducting numerical experiments to simulate the screw-propeller operation in free water. Practical value. It is established that the way of setting the project for simulating the screw-propeller operation in free water using the «sliding» grid boundary condition is the most practical one. The validity of this conclusion is confirmed by the results obtained during large number of numerical experiments on flow around the rotating screw-propeller at a given speed. The universality of such method lies in the possibility of its application during calculation of the propulsion/steering unit, which operates behind the ship hull.